(untitled) (Nexus International Journal of Science and Education, 2024)
The study aimed to determine the level of educational leadership management and the level of organizational commitment of public elementary school teachers. This study employed a non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. Two hundred fifty (250) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the educational leadership management was high while the level of organizational commitment of public elementary school teachers was also high. Moreover, the overall results disclosed that indicators for educational leadership management were positively correlated to the organizational commitment of public elementary school teachers. Further, results from the regression analysis revealed the following have a strong influence of educational leadership management on the organizational commitment of public elementary school teachers: instructional, democratic, coaching, and transformational style. It is recommended to provide opportunities for professional development and offer regular professional development opportunities that align with teachers' needs and aspirations. These can include workshops, seminars, conferences, or mentoring programs. Providing teachers with opportunities to grow professionally and enhance their skills can increase their commitment to the organization.